Charles Wright Mills’ Analysis of Political Dynasties in Indonesia in The 5.0 Era - Usman, Yosef; Losi, Anjelinus; Mirabela, Odiliana; Dagur, Oswaldus; Any, Anastasia (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2025)
This paper examines the phenomenon of political dynasty elite networks in Indonesia through the lens of Charles Wright Mills' thought. The growing tendency of political dynasties raises academic concerns as it narrows public participation and weakens democracy. Power is no longer contested through healthy democratic mechanisms but is instead inherited within closed circles of interconnected elites bound by family ties. This study employs a literature review method by analyzing Mills’ seminal work, The Power Elite (1956), combined with a Heideggerian phenomenological approach to understand the ongoing reality of power. The findings reveal that elites hold power not through public legitimacy but through domination by informal power networks. In this context, Indonesian democracy is reduced to mere formalities, while key strategic decisions remain in the hands of a select few elites detached from the interests of the people.